REDUCED BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF CARDIAC EVENTS AFTER MYOCARDIAL INFARCTION: A 6 MONTHS FOLLOW-UP STUDY. (June 2018) - Konstantinou, K.; Tsioufis, K.; Dimitriadis, K.; Mantzouranis, M.; Koumelli, A.; Fragoulis, C.; Kasiakogias, A.; Vogiatzakis, N.; Tolis, P.; Tolis, E.; Tousoulis, D.
Abstract : Objective: The impact of blood pressure variability (BPV) on cardiac function has been mainly examined through the prism of congestive heart failure and hypertension, but not in the setting of an acute coronary syndrome (ACS). The aim of this study is to determine the association between in-hospital short-term BPV and the development and aggravation of cardiac dysfunction in patients with acute myocardial infarction (AMI). Design and method: A total population of 57 AMI patients [74.5% male; mean age: 67.56 years;75.4% hypertensives]underwent 24hr ambulatory BP measurement during hospitalization.At 6 months a follow-up was scheduled for each patient in order to collect data on hospitalizations for heart failure (HF), but also to assess the overall cardiovascular outcome.The latter was defined as the composite end-point ofhospitalizations for heart failure (n = 8), decline in ejection fraction (EF%) compared to the in-hospital value (n = 11), deterioration of NYHA class (n = 3) and new onset of heart failure symptoms (n = 2). In-hospital BPV was assessedusing standard deviation (SD) and average real variability (ARV). The study population was divided intoa STEMI group (n = 24) and a non-STEMI (n = 33) one. Results: BPV was not associated with hospitalizations for HF. However, when the composite end-point was assessed, ARV of systolic BP demonstrated a significant negativeassociation [B = -0.430; odds ratio, 0.651; CI, 0.473–0.895 (P = 0.008)]in the total population. A relatively significant predictive roleof ARV was shown after splitting the population into the STEMI [B = −0.531; odds ratio, 0.588; CI, 0.339–1.019 (P = 0.058)]and non-STEMI group[B = −0.4; odds ratio, 0.670; CI, 0.443–1.014 (P = 0.058)]. Multinomial logistic regression analysis of incidence of cardiovascular events highlightedsystolic BP ARVas the onlyindependent predictor during a 6-month follow-up [B = −0.508; odds ratio, 0.602; CI, 0.407–0.891 (P = 0.011)] regardless the ACS type. Conclusions: In the setting of ACS, reduced in-hospital systolic BP ARV was associated with cardiovascular morbidity during the 6 months of follow-up. This finding could be attributed to a dysautonomic state of the cardiovascular system related to the pathophysiology of ACS, linking BP regulation mechanisms to worse overall outcome in this high risk setting.